Assessing Credit Performance and Risk Management Outcomes in Nepalese Commercial Banks: A Ten-Year Sector-Wide Analysis - Basnet, Shahadev; Kaur, Kamaljeet (Journal of Advanced Academic Research, 2026)
The paper has studied credit performance, risk management, profitability and capital adequacy of Nepalese commercial banks using a ten-year sector-wide analysis. Financial intermediation in Nepal has been primarily facilitated by the commercial banks thus effectiveness of credit bandaging and capital strength are of paramount importance to financial stability. The research design has assumed the descriptive quantitative research design employing secondary data which is collected on all 20 Class A commercial banks in the two fiscal years 2072/73 to 2081/82. Credit performance has been determined in terms of the Credit Deposit Ratio and profitability and solvency have been determined in terms of ROA, ROE, EPS and with the Capital Adequacy Ratio. Empirical examination has been done using descriptive statistics, correlation analysis, trend analysis, and linear regression. The results have shown that the profitability of most banks has been relatively stable and moderate in nature despite possessing a significantly different range of variation among banks. There is consequent strong relationship between credit deployment and profits performance and little relationship between capital adequacy and profitability indicators. The regression findings have affirmed that capital adequacy changes have not been significantly explained with profits and credit variables. This paper has reached a conclusion that instead of excessive capitalization, sustainable banking performance in Nepal has hinged upon the management of credit risk which is balanced, sound lending practices and good utilization of capital.